Normativism of Islamic Law in the Akkattere Hajj Ritual of South Sulawesi’s Ammatoa Community - Misbahuddin, Misbahuddin; Ys, Arba'iyah; Cahyani, Andi Intan; Samsudin, Titin; Fuad, Iwan Zainul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The profound impact of cultural and religious modernity on various aspects of life has brought about significant changes in regional akkattere traditions in Ammatoa society. According to this hadith, the pilgrimage which is in harmony, the conditions and obligations are in accordance with Islamic law, and which must be performed at a certain time and place, can be completed easily through the akkattere ritual. This research is an empirical law using an anthropological approach to Islamic law. The purpose of this study is to examine the incorporation of customary values and Islamic law in the Akkattere tradition of the Ammatoa community in the region, and to evaluate its impact. Data was collected using interviews and literature studies. The research was conducted in Tanah Towa Village in Kajang District, Bulukumba Regency, South Sulawesi Province. The research concluded that the akkatere ritual obviated the need to wait in long lines or have the financial resources to perform the pilgrimage to the holy land of Mecca. Based on the findings of this study, anthropologically the akkattere traditional law is the result of a dialectic between Islam and local traditions and has resulted in new local pilgrimage practices, which is now a religious characteristic of the Ammatoa people. Nonetheless, the understanding of Hajj by the Ammatoa community has deviated substantially from the normatism of Islamic law, so that it fundamentally influences aspects of religious belief and ideology.